Variation in groundwater geochemistry and microbial communities in the High Plains aquifer system, south-central Kansas - Richard, Alexandria Demi (Kansas State University, 2018)
Groundwater from the High Plains aquifer is vital for food production and a growing human population in the Great Plains region of the United States. Understanding how groundwater quality is changing in response to anthropogenic and natural processes is critical to effectively managing this resource. Our study considers variation in groundwater geochemistry in the Great Bend Prairie aquifer, a portion of the High Plains aquifer in southcentral Kansas. We collected samples during summer 2016 from 24 monitoring wells and compared our results to data collected previously from the same wells from 1979 to 1987. We sampled 13 wells screened in the upper portion of the aquifer (avg. depth 72 ft), 10 wells screened near the aquifer base (avg. depth 141 ft), and one well screened in underlying bedrock. Compared to initial samples, samples we collected tended to have higher total dissolved solids (TDS) and nitrate content, particularly those we collected from the upper aquifer. Compared to initial samples, TDS was 78 mg/L higher in samples we collected from the upper aquifer and 373 mg/L lower in samples we collected from the aquifer base on average. Nitrate exceeded the U.S. standard for public supplies of drinking water (10 mg/L as N) in seven of the samples we collected, compared to only two samples collected previously. Compared to previous samples, nitrate concentrations were 9.5 and 3.9 mg/L as N higher on average in samples collected from the upper aquifer and aquifer base, respectively. Based on a mixing analysis, variation in the salinity of our samples primarily reflects the dilution of natural Permian brines by freshwater recharge throughout the area. However, salinity decreases observed in four samples reflects flushing of initial oil brine contamination over time, salinity increases in two samples may be due to evapotranspiration, and salinity increases in two samples may reflect migration of oil-brine contamination towards the site. Stable nitrogen (¹⁵N/¹⁴N) and oxygen (¹⁸O/¹⁶O) isotope ratios in our samples primarily fall within the range typical of nitrification of ammonium-based fertilizers with potential contributions from manure or sewage. In our analysis of the microbial community, we observed groups capable of denitrification, including genera within Nitrospirae, Firmicutes, and Proteobacteria. Despite their presence, our results demonstrate that water quality in the aquifer has degraded over the past 30 to 40 years due to nitrate accumulation.
Keywords: Geochemistry; Geomicrobiology; Groundwater; High Plains aquifer; Great Bend Prairie aquifer; Bromide/chloride ratios